HUBUNGAN SIKAP PERAWAT DENGAN PELAKSANAAN IDENTIFIKASI DALAM PATIENT SAFETY DI RUANGAN RAWATINAP RUMAH SAKIT MITRA TAHUN 2025 - Paranita Utama; Pela Medyasa (Nightingale: Journal of Nursing, 2025)
Based on the IKP report at Mitra Hospital in 2022, there were 3 cases of KTD, 9 cases of KNC, and 2 cases of KTC. This study aimed to determine the relationship between nurses’ attitudes and the implementation of patient identification in patient safety at the inpatient ward of Mitra Hospital in 2025. The research method used was an observational analytic survey with a cross-sectional design. The sampling technique applied was total sampling, with a total of 36 respondents. Data were analyzed using the Spearman Rho statistical test. The results showed that among respondents with poor attitudes, patient identification was also poorly performed in 5 respondents (38.5%) and fairly well in 8 respondents (61.5%). Meanwhile, the majority of respondents with good attitudes performed patient identification fairly well in 9 respondents (39.1%), well in 11 respondents (47.8%), and very well in 3 respondents (13%). The Spearman Rho analysis revealed an r value = 0.680 with a p value = 0.001. Thus, it can be concluded that there is a significant relationship between nurses’ attitudes and the implementation of patient identification in patient safety at the inpatient ward of Mitra Hospital in 2025. The results of this study are expected to enhance nurses’ knowledge regarding patient identification as part of patient safety practices.